High discounts and low fundamental surplus: An equivalence result for unemployment fluctuations - Indrajit Mitra; Taeuk Seo; Yu Xu (Federal Reserve Bank of Atlanta, 2021)
Ljungqvist and Sargent (2017) (LS) show that unemployment fluctuations can be understood in terms of a quantity they call the "fundamental surplus." However, their analysis ignores risk premia, a force that Hall (2017) shows is important in understanding unemployment fluctuations. We show how the LS framework can be adapted to incorporate risk premia. We derive an equivalence result that relates parameters in economies with risk premia to those of an artificial economy without risk premia. We show how to use properties of the artificial economy to deduce how risk premia affect unemployment dynamics in the original economy.
Keywords: E23; E24; E32; E44; J23; J24; J31; J41; J63; 330; risk premia; fundamental surplus; time-varying discounts; unemployment fluctuations